The H+N2O -> OH((2)Pi(Omega),upsilon ',N ')+N-2 reaction: OH rotational angular momentum polarization - Brouard, M; Gatenby, S; Joseph, D; Vallance, C (2000)
The OH state-resolved angular momentum polarization generated by the H+N2O reaction has been investigated at a mean collision energy of 1.5 eV. The data were obtained under room temperature bulb conditions using 225 nm photolysis of H2S to generate translationally excited H atoms, and employed Doppler-resolved laser induced fluorescence to probe the nascent OH reaction products. The measurements revealed the OH rotational angular momentum, j′, to be aligned in the scattering plane (i.e., in the plane containing the reactant and product relative velocity vectors, k and k′). Furthermore, j′ was found to be preferentially aligned parallel to k′, particularly for lower OH rotational states. Out-of-plane torsional forces have been shown, therefore, to play an important role in generating OH rotation as the fragments separate. The new data are discussed in light of previously published studies of the title reaction, both from our own laboratory, and from those of other workers. Insight into the reaction mechanism is provided by comparison with the photodissociation dynamics of HN3, which helps, in particular, to clarify the origin of the propeller-like OH rotational angular momentum polarization. © 2000 American Institute of Physics.